Customer Journey Mapping In The Multi-Platform Era: A Touchpoint Analysis Of Purchase Decision-Making - Indra Putu Desa Nota; Engkus (STIE Amkop Makassar, 2026)
The rapid proliferation of digital platforms has fundamentally transformed how consumers discover, evaluate, and purchase products. This study investigates the role of multi-platform touchpoints in shaping customer purchase decisions through the lens of Customer Journey Mapping (CJM). Drawing on a mixed-methods design, data were collected from 385 online shoppers in Indonesia through structured questionnaires and supplemented by 20 in-depth interviews. Structural Equation Modelling (SEM) was employed to quantify the relative influence of each touchpoint across five journey stages: awareness, consideration, evaluation, purchase, and post-purchase loyalty. Findings reveal that social media platforms, particularly Instagram and TikTok, exert the strongest influence during the awareness stage (β = 0.742, p < 0.001), while e-commerce platforms dominate at the evaluation and purchase stages. Customer reviews and ratings emerged as the most persuasive touchpoint across all stages (β = 0.764). The study further identifies critical cross-platform switching patterns, demonstrating that consumers typically engage an average of 4.7 touchpoints before completing a purchase. These findings provide actionable insights for marketing managers seeking to optimise omnichannel strategies and allocate resources across the customer journey